2011
DOI: 10.1002/hyp.8126
|View full text |Cite
|
Sign up to set email alerts
|

Cloud water interception in the high altitude tree heath forest (Erica arborea L.) of Paul da Serra Massif (Madeira, Portugal)

Abstract: Abstract:Cloud water interception (CWI) occurs when cloud droplets are blown against the forest canopy, where they are retained on the vegetation surface, forming larger water droplets that drip into the forest floor. CWI was measured from 1 October 1997 to 30 September 1999, on a first-line tree heath (Erica arborea), at Bica da Cana, Madeira Island. Rainfall was corrected for wind-loss effect and compared with throughfall and other climatological normals. The CWI depletion rate along a forest stand transect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 45 publications
3
25
0
2
Order By: Relevance
“…In sites with frequent fog, such as Cunha, net precipitation can also overcome rainfall as a result of occult precipitation, i.e., capture and dripping of water from the fog through the treetops (GOMEZ-PERALTA et al, 2008;PRADA et al, 2012). An indication of the occurrence of occult precipitation in eucalyptus is the fact that of the 415 events recorded during the study, throughfall water was collected without the presence of gross precipitation on 16 occasions, totaling 3.7 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sites with frequent fog, such as Cunha, net precipitation can also overcome rainfall as a result of occult precipitation, i.e., capture and dripping of water from the fog through the treetops (GOMEZ-PERALTA et al, 2008;PRADA et al, 2012). An indication of the occurrence of occult precipitation in eucalyptus is the fact that of the 415 events recorded during the study, throughfall water was collected without the presence of gross precipitation on 16 occasions, totaling 3.7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Although no anemometric measurements were taken in the present study, during field observations it was observed that the crowns of eucalyptus trees were more susceptible to wind action than pine trees. The movement of the leaves and branches is essential for the dripping of intercepted fog water (PRADA et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Prada et al . () quantified cloud water interception or fog water dripping from a heath tree ( Erica arborea L.) forest in Bica da Cana (Madeira): maximum values of around 200 mm day −1 , mean daily values of 28 mm day −1 and average yearly cumulative fog values of 4169 mm year −1 during a 3‐year period (1997–1999). These data were obtained using only two gauges (0.357 m diameter; 0.10 m 2 collecting area); one placed leeward and the other windward under an individual exposed E. arborea tree.…”
Section: Comparison Of Prada Et Al () With Previous Related Studies mentioning
confidence: 97%
“…Although Prada et al . () acknowledged the insufficiency of the number of gauges they used, they claim to have checked data ‘consistency’ by comparing their fixed arrangement with data obtained using three larger (0.28 m 2 collecting area) roving gauges. No details about the methodology (relocation frequency, number of roving positions, spatial location of repositioned gauges, etc.…”
Section: Comparison Of Prada Et Al () With Previous Related Studies mentioning
confidence: 99%
See 1 more Smart Citation